1998
DOI: 10.1074/jbc.273.18.10926
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Thyroid Hormone Receptors by Protein Kinase A Regulates DNA Recognition by Specific Inhibition of Receptor Monomer Binding

Abstract: Thyroid hormone receptor (T3R) ␣-1 and its oncogenic derivative, the v-ERB A protein, are phosphorylated by cAMP-dependent protein kinase A. Although this phosphorylation appears to be necessary for the oncogenic properties of v-ERB A, the mechanism by which phosphorylation influences the functions of v-ERB A and of the normal T3R has not been established. The protein kinase A phosphorylation site in T3R␣-1 is within a domain that is known to contribute to the DNA recognition properties of these receptors. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…Although the TRs are ligand-activated receptors, they can also be functionally regulated by phosphorylation (Lin et al, 1992;Bhat et al, 1994;Sugawara et al, 1994;Ting et al, 1997;Tzagarakis-Foster and Privalsky, 1998;Davis et al, 2000;Chen et al, 2003). Phosphorylation and dephosphorylation reactions are accomplished by multiple kinases and phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TRs are ligand-activated receptors, they can also be functionally regulated by phosphorylation (Lin et al, 1992;Bhat et al, 1994;Sugawara et al, 1994;Ting et al, 1997;Tzagarakis-Foster and Privalsky, 1998;Davis et al, 2000;Chen et al, 2003). Phosphorylation and dephosphorylation reactions are accomplished by multiple kinases and phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the HNF4 (NR2A1) DNA-binding domain enhances DNA binding (41), while phosphorylation of both NGF1-B (NR4A1) and T 3 Ra1 (NR1A1) in the DNA-binding domain by PKA inhibits DNA binding (42,43). PKC family members directly phosphorylate vitamin D receptor (VDR, NR1I1), retinoic acid receptor a (RARa, NR1B1), and COUP-TF1 (NR2F1) in the DNA-binding domain, with distinct transcriptional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that other transcription factors may be targets of Cdk8 activity as its yeast homolog, Srb10, is capable of modulating transcription factor activity (Chi et al, 2001;Nelson et al, 2003). This could include TRs themselves because phosphorylation can lead to protein stabilization and signal potentiation as we have observed in anuran tail tissues (Ji et al, 2007) and others have observed in mammalian cells (Jones et al, 1994;Ting et al, 1997;Tzagarakis-Foster and Privalsky, 1998;KunoMurata et al, 2000;Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%